Open water swimming performance - Hara, R.; Muraoka, I. (Sports Performance, 2015)
Open water swimming is defined as any swimming competition that takes place in rivers, lakes, oceans, or water channels. Since the inclusion of open water swimming as an Olympic event in 2008, it has steadily been gaining popularity worldwide. Many studies have focused on the risks involved in open water swimming events. The purpose of this chapter is to review and shed light on the risks and performance factors of open water swimming. It is hoped that this information will improve both safety and performance worldwide. Most studies have reported that open water swimming involves risks of hypothermia and afterdrop. Since hypothermia can lead to death, adequate medical preparations must be made in order to attend to emergency cases. Another possible risk involved with the sport is heat stroke. Fédération Internationale de Natation (FINA) sets rules for water temperature on race days. However, some studies have found that racing under the FINA rules can still leave some swimmers vulnerable to heat stroke. Special attention must be given to the race conditions and should include the possibility of providing food to contestants during the race. The United States and Brazil performed experiments with their top athletes to investigate physiological stresses in relation to race conditions. These studies suggested that pre core temperature and capillary glycemia were related to their race times. Because these studies were reported in 2004 (VanHeest et al. 2004), further investigation must be conducted in open water swimmers to determine the factors that can maximize performance in this event.